Analisis Faktor - Faktor Yang Mempengaruhi Non Performing Loan (NPL) Kredit Pada Bank Umum di Indonesia (Studi Pada Bank Umum Yang Terdaftar di Bei Periode 2016 - 2017) - Menik Agustiningtyas (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2018)
Banks generally in carrying out their operations to obtain business results are always faced with a risk. One of the risks experienced by a Bank is the ratio of non-performing loans or what is called Non NPL. Based on Bank Indonesia regulations, banks have a potentially dangerous if the bank has an NPL ratio of more than 5%. This study aims to analyze the influence of Inflation, CAR, NIM, and BOPO on NPLs in Commercial Banks in Indonesia for the 2016-2017 period. This research was conducted using quantitative methods. The data used in this study are financial statements of 20 commercial banks in 2016-2017 on the official Indonesian Stock Exchange (IDX) website, this study uses multiple linear regression analysis as a data analysis tool. From the results of partial analysis of Inflation 0.300 ≥ 0.05 and NIM 0.190 ≥ 0.05, which means that there is no significant effect on Non-Performing Loans (NPL), while CAR 0.007 ≤ 0.05, but the T value is -2.879 which means that it is influential but not significant to NPL and BOPO 0.035 ≤ 0.05 has a significant influence on NPL. While simultaneously showing that Inflation, CAR, NIM and BOPO have a significant influence on NPLs of 53.1%.Keywords: Non Performing Loans (NPL), Inflation, Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), and Operational Income Operating Costs (BOPO)